2022
DOI: 10.1007/s00268-022-06649-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evolving Trends in the Management of Acute Appendicitis During COVID‐19 Waves: The ACIE Appy II Study

Abstract: Background In 2020, ACIE Appy study showed that COVID-19 pandemic heavily affected the management of patients with acute appendicitis (AA) worldwide, with an increased rate of non-operative management (NOM) strategies and a trend toward open surgery due to concern of virus transmission by laparoscopy and controversial recommendations on this issue. The aim of this study was to survey again the same group of surgeons to assess if any difference in management attitudes of AA had occurred in the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The majority of surgeons still consider NOM an ineffective treatment for uncomplicated appendicitis, even in the four participating hospitals. This is well reflected by two recent large international surveys reporting that NOM is the preferred treatment for only 14% of respondents [ 17 , 18 ]. When compared to patients receiving NOM, patients who underwent upfront appendectomy had higher WBC count and AIR score, more frequent detection of appendicolith and free fluid at ultrasound/CT scan.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of surgeons still consider NOM an ineffective treatment for uncomplicated appendicitis, even in the four participating hospitals. This is well reflected by two recent large international surveys reporting that NOM is the preferred treatment for only 14% of respondents [ 17 , 18 ]. When compared to patients receiving NOM, patients who underwent upfront appendectomy had higher WBC count and AIR score, more frequent detection of appendicolith and free fluid at ultrasound/CT scan.…”
Section: Discussionmentioning
confidence: 93%
“…The deferral of elective procedure during COVID-19 pandemics has created a backlog of millions of surgical procedures, an unexpected challenge for healthcare system worldwide ( 9 ). Even in urgent surgery, a shift toward nonoperative management has occurred as revealed by Stavridis et al in their systematic review on acute cholecystitis management, a similar trend observed in the management of acute appendicitis ( 10 ).…”
mentioning
confidence: 81%
“…We thank Yang and colleagues for their correspondence highlighting the results of ACIE Appy II study [ 1 ] and proposing the endoscopic retrograde appendicitis therapy (ERAT) as a new tool to improve the management of acute appendicitis (AA) even during pandemic times.…”
mentioning
confidence: 99%
“…We did not include any questions about ERAT in the ACIE Appy studies [ 1 , 2 ] because no guideline or scientific society recommended it for AA at the time of the study [ 3 , 4 ].…”
mentioning
confidence: 99%